2013
DOI: 10.4314/ajcem.v14i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and immune status of HIV/HBV co-infected pregnant women

Abstract: HIV/HBV co-infection places patients at high risk of liver-related morbidity and mortality and the interaction of the two viruses can further complicate treatment. Pregnant women are especially at high risk for increased morbidity and mortality due to infection, and information about HIV/HBV co-infection in pregnant women is scanty. This study examined the occurrence of HBV antibodies in HIV-1 positive pregnant women and the relationship to Ante-retroviral therapy (ART) and other demographic characteristics. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 30 publications
2
17
2
Order By: Relevance
“…In light of this, we conducted a region based analysis of our data, the NW region of the country appeared to have the highest (41%) prevalence of HBV/ HIV co-infection. This finding is, however, constrained by the fact that only two studies were conducted in the region and both of them were from the same center and on similar participants, yet yielding a wide difference in HBV/HIV co-infection prevalence (12% [47] and 70.3% [37]). Otherwise, the other regions had prevalences close to the overall prevalence HBV/HIV co-infection we found in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, we conducted a region based analysis of our data, the NW region of the country appeared to have the highest (41%) prevalence of HBV/ HIV co-infection. This finding is, however, constrained by the fact that only two studies were conducted in the region and both of them were from the same center and on similar participants, yet yielding a wide difference in HBV/HIV co-infection prevalence (12% [47] and 70.3% [37]). Otherwise, the other regions had prevalences close to the overall prevalence HBV/HIV co-infection we found in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity chi-squared was 1610.84 (d.f.=33) p=0.000, I-squared (variation in ES attributable to heterogeneity) was 98.0% and estimate of between-study variance Tau-squared was 0.0043. Ajayiet al [22] Adeshina et al [23] Adewole et al [24] Adoga et al [25] Eke et al [26] Ajayi et al [27] Ashir et al [28] Balogun et al [29] Buseri [30] Diwe et al [31] Ejele et al [32] Nwolisa et al [33] Anigilaje et al [34] Idoko et al [35] Ladep et al [36] Lar et al [37] Mustapha et al [38] Nwokedi et al [39] Okocha et al [40] Oronsaye et al [41] Otegbayo [42] Tremeau-Bravard et al [43] Uneke et al [44] AkyalaIshaku et al [45] Bello et al [46] Denue et al [47] Ekanem et al [48] Hamza et al [49] Opara-Morrison et al [50] Omonkhelin et al [51] Frank -Petersideet al [52] Sadoh et al [53] Okeke et al [54] Odunukwe et al The REM estimate of prevalence among HIV-infected patients from 33 studies was 15% (95% CI 13-17%) (Figure 3). There was a publication bias in Egger's, and Begg's testing (Begg's test, p=0.003; Egger's test, p=0.000).…”
Section: Findings From the Meta-analysismentioning
confidence: 99%
“…Whereas in most SSA countries HIV is routinely tested for in pregnant women attending antenatal care (ANC), HBsAg screening in the same cohort is not routine despite their overlapping routes of transmission [ 18 – 20 ]. This has hampered the design of interventions to mitigate the effect of HBV–HIV co-infection in pregnancy since the epidemiological data on the HBV–HIV co-infection among pregnant woman in SSA is scanty [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, pregnant women co-infected with HIV-HBV has mean CD4 count of 361cells/µl, but statistically, there was no association between HIV-HBV co-infection and the immune status of the women (p>0.05). Compared with the study carried out in Jos, Lar and his colleagues reported a CD4 count of 300cells/mm 3 and below, among pregnant women co-infected with HIV-HBV (Lar et al, 2013). When the mean CD4 count of HIV mono-infected (419cells/µl) is compared with the HIV-HBV co-infected (361cells/µl) study participants, there was decrease in the mean CD4 count of HIV-HBV co-infected pregnant women.…”
Section: Discussionmentioning
confidence: 73%